Effects of 10 KM run on foot morphology and bilateral symmetry in male recreational runners - Mo, Shiwei; Lu, Feifei; Li, Chuhao; Zhao, Huan (Frontiers in Bioengineering and Biotechnology, 2024)
Foot morphology and arch integrity do not remain constant during a running bout. Previous studies have reported inconsistent changes in foot sizes and arch parameters and this discrepancy may be related to the variation in their test duration, e.g., 15-minute treadmill run vs. 30KM trial. Hence, this study sought to evaluate the change in foot morphology, arch integrity and bilateral symmetry after a 10KM run among 19 male recreational runners. Before and after the run, a portable foot scanner was used to capture the 3-dimensional foot images and measure foot dimensions in both weight-bearing and non-weight-bearing conditions. Foot arch integrity was quantified by arch height ratio, arch height index, and arch stiffness index (ASI). Bilateral symmetry was evaluated by calculating the symmetry index. Increased foot length (p=0.007; 𝜂 𝑝 2 =0.18) and decreased ball girth (p=0.038; 𝜂 𝑝 2 =0.11) were demonstrated following the run with absolute differences of less than 2 mm. Navicular height, dorsum height, arch height ratio and arch height index significantly decreased after the run (p<0.001; 𝜂 𝑝 2 ≥0.30) whereas ASI increased (p<0.001, 𝜂 𝑝 2 = 0.33) and navicular height drop reduced (p<0.001, 𝜂 𝑝 2 = 0.37). Significances of symmetry index were only demonstrated for navicular height (p=0.019, effect size=0.37) and arch height ratio (p=0.019, effect size=0.42). A few changes in foot morphology were detected but a reduction in foot arch height was demonstrated, which may give shoe manufacturers insights into shoe design. Male recreational runners were recommended to choose shoes with arch support for maintaining foot arch function during a 10KM run.